Molecular characterization, tissue distribution, and ultrastructural localization of adipokinetic hormones in the CNS of the firebug Pyrrhocoris apterus (Heteroptera, Insecta) - Kodrík, Dalibor; Stašková, Tereza; Jedličková, Veronika; Weyda, František; Závodská, Radka; Pflegerová, Jitka (General and comparative endocrinology, 2015)
Adipokinetic hormones (AKHs) are a group of insect metabolic neurohormones, synthesized and released from an endocrine retrocerebral gland, the corpus cardiacum (CC). Small amounts of AKH have also been identified in the brain, although their role in this organ is not clear. To address this gap in the knowledge about insect brain biology, we studied the nucleotide sequence, tissue distribution, and subcellular localization of AKHs in the brain and CC of the firebug Pyrrhocoris apterus. This insect expresses two AKHs; the octapeptides Pyrap-AKH and Peram-CAH-II, the presence of which was documented in the both studied organs. In situ hybridization and quantitative reverse-transcription (q-RT)-PCR revealed the expression of the genes encoding for both AKHs not only in the CC, but also in brain. Electron microscopy analysis of the brain revealed the presence of these hormones in specialized secretory granules localized predominantly in the cellular bodies of neurons. The hormones might be transported from the granules into the axons, where they could play a role in neuronal signaling. Under acute stress induced by the injection of 3μmol KCl, the level of AKHs in the brain increased to a greater extent than that in the CC. These results might indicate an enhanced role of brain-derived AKHs in defence reaction under acute stress situations.
Keywords: Sequence Homology, Amino Acid; Pyrrolidonecarboxylic Acid; oligopeptidy; Central Nervous System; Gene Expression; Molecular Sequence Data; sekvence aminokyselin; Base Sequence; Cloning, Molecular; Animals; hmyzí hormony; exprese genu; kyselina pyrrolidonkarboxylová; sekvenční homologie aminokyselin; centrální nervový systém; zvířata; Stress, Physiological; sekvence nukleotidů; Heteroptera; klonování DNA; fyziologický stres; tkáňová distribuce; Oligopeptides; Amino Acid Sequence; Insect Hormones; Tissue Distribution; molekulární sekvence - údaje